2015
DOI: 10.1007/s10557-015-6604-7
|View full text |Cite
|
Sign up to set email alerts
|

Nifekalant Versus Amiodarone in the Treatment of Cardiac Arrest: an Experimental Study in a Swine Model of Prolonged Ventricular Fibrillation

Abstract: Nifekalant showed a more favorable hemodynamic profile and improved survival compared to amiodarone and saline in this swine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In the present analysis, there was no statistically significant difference in short-term or long-term survival between the AMD- and NIF-treated patients or between the RCT and non-RCT studies. The results of an experiment conducted in pigs showed that NIF caused a higher survival rate than AMD does 39 . However, another study using pigs 40 and some clinical trials 19 – 21 , 29 – 36 have indicated that AMD and NIF have a similar efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, there was no statistically significant difference in short-term or long-term survival between the AMD- and NIF-treated patients or between the RCT and non-RCT studies. The results of an experiment conducted in pigs showed that NIF caused a higher survival rate than AMD does 39 . However, another study using pigs 40 and some clinical trials 19 – 21 , 29 – 36 have indicated that AMD and NIF have a similar efficacy.…”
Section: Discussionmentioning
confidence: 99%
“… 12 This may be related to the efficacy of amiodarone in preventing ventricular tachyarrhythmias in the immediate postresuscitation period (refibrillation) or reversal of these transient adverse events. 18 Similarly, the benefit of lidocaine in cardiac arrest most likely relates to its efficacy in minimizing arrhythmia recurrences, once an organized rhythm is restored by other means such as defibrillation. 19 …”
Section: Discussionmentioning
confidence: 99%
“…The optimal time for application (early versus late) during CPR is not known. There are only a few studies of early application for amiodarone, which show equivocal results578111213.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoints were firstly, ROSC (defined as maintenance of systolic BP ≥ 60 mmHg for a minimum of 5 minutes) and secondly, sustained ROSC, defined as persistent spontaneous circulation until 120 min after successful defibrillation7.…”
Section: Methodsmentioning
confidence: 99%